Comparison of effectiveness between a conventional catheter and a manual commercial catheter: randomized trial of simulation of intraosseous access in a biological model (2019)
Introduction: In the emergency services an action of paramount importance in critically ill patients is to obtain an early vascular access. When vascular access is not established, an intraosseous route should be obtained; otherwise, the mortality of these critically ill patients is almost 100%. In Colombia, the intraosseous access is not used because of the high costs of the devices and the lack of training of the healthcare staff to conduct the procedure.Objective: To determine the efficacy of a low-cost device to establish intraosseous access.Materials and methods: Quantitative approach, experimental design in a simulated environment with chicken tarsus and metatarsus. An analysis was conducted using frequency tables and central tendency measurements. Likewise, further analyses were done using Fisher's exact test, Chi2, and Mann-Whitney test.Results: A total of 99% of the procedures were successful with both catheters. The average time for intraosseous access was 6.6 seconds with Insyte 14 catheter and 4.7 seconds with Din 1515x Illinois Desch device (P=0.001). There were no significant differences in the number of attempts to secure a successful intraosseous access using any of the 2 devices (P=0.56).Conclusion: There was no significant difference between the Ci 14 and the Si 14 catheter to establish a successful intraosseous access in the chicken tarsus and metatarsus in a simulated environment. © 2019 Sociedad Colombiana de Anestesiología y Reanimación (S.C.A.R.E.).